The battle over the flag: protest, community opposition, and silence in the Mennonite colleges in Kansas during the Vietnam War - Ottoson, Robin Edith Deich (Kansas State University, 2018)
This study examines how three Mennonite colleges in Kansas struggled with issues of church and state during the Vietnam War as they attempted to express patriotism while remaining true to their Anabaptist theological heritage and commitments. It considers how the pressures of an undeclared war in Vietnam and acculturation into the greater American society produced tension within these colleges and also evaluates whether these forces eroded or sharpened their peace positions and those of their parent denominations. Allowing for close analysis of three groups that derive from the same theological tradition, but which have struggled with how to express their dual doctrines of nonresistance and nonconformity in regard to the American state and society, the investigation considers both the motivations for and political experience of dissent by these people previously opposed to political involvement. This study examines why the three campuses chose different responses to this dilemma and argues that their actions depended not only on students, but also were influenced by the leadership of faculty and administration, decisions by the three parent denominations, and pressures exerted by the towns in which they were located. As such, this study relies on a thick social analysis to explore what acculturation meant for Mennonites struggling to emerge from isolation and to be faithful to their Christian commitments. It offers an answer to the historiography that locates antiwar protest as a chiefly secular exercise and breaks new ground by arguing that even theologically conservative religious groups opposed the war and demonstrated against it because of their convictions and commitment. Moreover, it also explores the pressures exerted by Kansans on these groups and why two of the three were willing to raise questions and perform protests of a wide variety that risked the protected status extended to their draft-age young men. It also begins to fill a gap in the historical literature on Mennonites in central Kansas during the Vietnam War, describing the diverse responses by the different colleges and considering how the war challenged denominational attitudes about their historic faith and its relationship to government. In the case of one school in particular, the analysis also will indicate that the college had not completely resolved the tensions between church and state, but only postponed their resolution to the next decade. Finally, the study will lay groundwork for further investigation and argumentation regarding the abilities of the main Mennonite groups to experiment with and redefine non-conformity in regard to issues of church and state in the United States and the contested nature of antiwar unrest and protest in twentieth-century America. This dissertation incorporates the publication by Robin Deich Ottoson, “The Battle Over the Flag: Protest, Community Opposition, and Silence in the Mennonite Colleges in Kansas during the Vietnam War,” Journal of Church and State, 52, no. 4 (October 2010), 686–711, https://doi.org/10.1093/jcs/csq106. Used with permission by Oxford University Press and the J.M. Dawson Institute of Church-State Studies at Baylor University, this is the first comparative study of Mennonite college protest during the Vietnam War.
Keywords: Vietnam War; Mennonite colleges; KansasAntiwar protest